A STUDY OF TECHNO-PEDAGOGICAL CONTENT COMPETENCY AMONG GOVERNMENT AND PRIVATE SECONDARY SCHOOL TEACHERS - Mittal, Ranjana; Dubey, Pramila (International Journal of Research -GRANTHAALAYAH, 2025)
The present study aims to investigate the level of techno-pedagogical content competency among secondary school teachers with specific focus on the comparison between government and private institutions. The descriptive survey method was employed, and a sample of 300 secondary school teachers (150 male and 150 female) from Jaipur district was selected through simple random sampling. Data were collected using the Teachers’ Techno-Pedagogical Competency Scale developed by S. Rajashekar and K. Sathiyaraj (2013). The statistical techniques applied for data analysis included Mean, Standard Deviation, and Critical Ratio. The findings of the study revealed that the overall techno-pedagogical content competency of teachers was significantly higher than the expected average level. Furthermore, no significant difference was observed in competency levels between government and private school teachers, indicating that school type does not strongly influence teachers’ integration of technology, pedagogy, and content knowledge. The study concludes that teachers are adequately prepared to meet the demands of technology-integrated teaching. Based on the findings, suggestions for continuous professional development, blended learning adoption, subject-specific digital training, and institutional support have been proposed. This research contributes to the growing body of knowledge on teacher preparedness for digital education and highlights the need for sustained professional development and resource support to strengthen techno-pedagogical competencies across educational contexts.